1999
DOI: 10.1083/jcb.147.7.1431
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Proteins Tia-1 and Tiar Link the Phosphorylation of Eif-2α to the Assembly of Mammalian Stress Granules

Abstract: In response to environmental stress, the related RNA-binding proteins TIA-1 and TIAR colocalize with poly(A)+ RNA at cytoplasmic foci that resemble the stress granules (SGs) that harbor untranslated mRNAs in heat shocked plant cells (Nover et al. 1989; Nover et al. 1983; Scharf et al. 1998). The accumulation of untranslated mRNA at SGs is reversible in cells that recover from a sublethal stress, but irreversible in cells subjected to a lethal stress. We have found that the assembly of TIA-1/R+ SGs is initiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
1,377
1
20

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,116 publications
(1,450 citation statements)
references
References 52 publications
52
1,377
1
20
Order By: Relevance
“…In a separate study, Williams et al showed prolonged tumour growth after radiotherapy in a tumour line that is null for HIF1β (also known as ARNT), and therefore unable to render a HIF1 response 139 . The second mechanism of HIF1α stabilization after reoxygenation was related to stress granules 140 . These are protein-mRNA complexes that form in cells during periods of stress and prevent the cell from using energy for protein translation.…”
Section: Effects Of Radiation Therapy On Hif1 Activitymentioning
confidence: 99%
“…In a separate study, Williams et al showed prolonged tumour growth after radiotherapy in a tumour line that is null for HIF1β (also known as ARNT), and therefore unable to render a HIF1 response 139 . The second mechanism of HIF1α stabilization after reoxygenation was related to stress granules 140 . These are protein-mRNA complexes that form in cells during periods of stress and prevent the cell from using energy for protein translation.…”
Section: Effects Of Radiation Therapy On Hif1 Activitymentioning
confidence: 99%
“…1c). Notably, ERG also colocalized with T-cell intracellular antigen-1 (TIA1) and TIA1-related protein (TIAR), two additional SG markers 25 ( Supplementary Fig. 1c).…”
Section: Erg Localizes To Pbs and Promotes Cytoplasmic Mrna Decaymentioning
confidence: 99%
“…De plus, en séquestrant les facteurs d'initiation de la traduction, les granules de stress contribuent à la répression de cette dernière. En effet, l'initiation de la traduction est inhibée dans la plupart des conditions induisant ces granules, comme les infections virales, le stress oxydant, les radiations ionisantes, les chocs thermiques et ischémiques, ainsi que les inhibiteurs du protéa-some [7,[11][12][13]. Cette inhibition fait intervenir la phosphorylation du facteur d'initiation de la traduction eIF2 (eukaryotic translation initiation factor 2) [14].…”
Section: Rôle Protecteur De Hri Vis-à-vis Des Précurseurs éRythroblasunclassified